Upaya Meningkatkan Hasil Belajar Passing Atas Pada Bola Voli Melalui Alat Peraga Audio Visual Pada Siswa Kelas VI SDN Lontar 481 Surabaya - Elfahmi, Dzulfikri Rusda; Ramadhani, Dyanisyaf; Astutik, Heni Yuni; Priambodo, Anung (Peneliti.net, 2024)
This research is for class VI of SDN LONTAR 481 Surabaya 2023/2024. The aim is to find out the results of learning certain passing movements in the volleyball invasion game through audiovisual media in the academic year. This research method uses the Classroom Action Research (PTK) method. The research was conducted in two cycles consisting of two meetings. The subjects of this research were 32 Class VI students at SDN LONTAR 481 Surabaya, consisting of 8 female students and 24 male students. The level of completion achieved is used in data analysis techniques. Before carrying out the first cycle measurements, the researcher first gave a pre-cycle test to determine the students' initial abilities. As a result, only 37.5% of students reached the learning completion threshold. After implementing Cycle I actions, learning outcomes increased. Of the 32 students, 2 students were able to reach the completion threshold with a percentage of 6.25%, 15 students were able to reach the completion threshold with a percentage of 46.8%, and 12 students were able to reach the completion threshold with a percentage of 46.8%. There were 3 students who did not reach the limit of learning completeness due to insufficient information (rate 9.4%), and in Cycle II there were 9 students who were able to reach the limit of learning completeness with very good information (rate 28.1%). The threshold for completeness in informed learning is expected to be achieved with a percentage of 56.2%, however there are still five students who have not reached the threshold for completeness in informed learning with a percentage of 15.6%.